INTERPRETASI SEJARAH LOKAL DAN PENGEMBANGAN JALUR WISATA DIGITAL BERBASIS QR CODE DI KAMPUNG KAUMAN YOGYAKARTA UNTUK SOLO TRAVELER - Makhasi, Ghifari Yuristiadhi Masyhari; Fakhrurrifqi, Muhammad (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2020)
Kauman kampong is a religious servant residence of Yogyakarta Sultanate which was formed along with the establishment of the Yogyakarta Sultanate Great Mosque in 1773. Muhammadiyah was founded in this kampong in 1912 which provided its own historical dynamics for this kampong. Since 2010 in Kauman kampong, Yogyakarta, the historical tour package "Tour de Muhammadiyah" has been re-branding to "Muhammadiyah Heritage Trip" in 2016. After ten years of developing guided tours in Kauman kampong, as technology develops, it is necessary to develop a digital basis, among others using a QR code that guides tourists to explore Kauman kampong as a solo-traveler without having to depend on the existence of a tour guide. This article offers the novelty of digitizing the historical travel route in Kauman kampong in four themes of interpretations, namely the history of the religious servants' village, the history of the Islamic women's movement, the history of the four national heroes from Kauman, and the history of Muhammadiyah's journey as an organization. It is hoped that this novelty can inspire the development of other historical regions in Indonesia to digitize local history in each place. This descriptive qualitative research collects data with participatory observation, interview, and documentation.